2009
DOI: 10.4049/jimmunol.0804314
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Regulates Fusion of Mononuclear Osteoclasts into Bone-Resorbing Osteoclasts by Activating the Ras/ERK Pathway

Abstract: Osteoclasts are multinucleated cells that are formed by the fusion of mononuclear osteoclasts, which is an essential process in bone resorption leading to bone remodeling. Herein we show that GM-CSF promoted the fusion of prefusion osteoclasts (pOCs). The expression of GM-CSF receptor-α was significantly up-regulated at the fusion stage of pOCs induced by RANKL. GM-CSF induced the expression of dendritic cell-specific transmembrane protein (DC-STAMP), which was mediated by inducing NFATc1 via induction of c-Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 42 publications
1
96
0
1
Order By: Relevance
“…DC-STAMP is a seven-transmembrane protein that was originally identified in dendritic cells (26). It has been reported that GM-CSF significantly induces pOC fusion by inducing DC-STAMP expression (21). This finding is consistent with ours, in which only DC-STAMP expression is significantly increased in the pOCs treated with IFN-γ; however, a number of studies have reported the role of fusion-related molecules in the multinucleation of pOCs (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…DC-STAMP is a seven-transmembrane protein that was originally identified in dendritic cells (26). It has been reported that GM-CSF significantly induces pOC fusion by inducing DC-STAMP expression (21). This finding is consistent with ours, in which only DC-STAMP expression is significantly increased in the pOCs treated with IFN-γ; however, a number of studies have reported the role of fusion-related molecules in the multinucleation of pOCs (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 80%
“…Bone marrow cells (BMCs) were collected from 5-week-old male ICR mice as described previously (21). The BMCs were suspended in α-MEM containing 10% FBS and antibiotics, and were cultured with M-CSF (10 ng/ml) for 1 day.…”
Section: Preparation Of Bone Marrow-derived Macrophages (Bmms)mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, multinucleated MA have been observed in tuberculosis (5), yeast infection (6), HIV infection (7), failure of orthopedic implants (8), and sarcoidosis (5,9). Accordingly, a number of cytokines produced by immune cells including GM-CSF, M-CSF, IL-4, IL-13, and IL-6, alone or in combination, have been reported to stimulate the appearance of multinucleated MA in various cell culture systems (4,(10)(11)(12)(13)(14). Despite the widespread observation of MA fusion in vitro and in vivo, the mechanisms underlying this process remain poorly understood.…”
mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 shown that NFATc1 expression was inhibited by the MEK inhibitor U0126 [32]. We could partially inhibit the IL-4 induction of CYP2E1 with the same MEK inhibitor (U0126), indicating the involvement of this protein kinase (Supplemental data, Fig.…”
Section: Page 17 Of 38mentioning
confidence: 99%